Penerapan Model Pembelajaran Cooperative Script untuk Meningkatkan Hasil Belajar IPS Siswa di SD Inpres Tumpu Jaya I - I Ketut Selamet (Jurnal Paedagogy, 2021)
This study aims to improve social studies learning outcomes through a cooperative script learning model in grade VI SD Inpres Tumpu Jaya I. This research method uses classroom action research with a spiral model from Kemmis and Mc Taggart using 2 cycles. The subjects of this study were 22 students of grade VI SD Inpres Tumpu Jaya I. The research instrument used item items and observation sheets. The data analysis technique used is descriptive comparative. The results of this study indicate that there is an increase in student social studies learning outcomes after using the cooperative script learning model. This is based on the comparison of the average score, namely 70.62: 79.19: 87.48 which means that there is an increase from pre-cycle to cycle II. Classical learning completeness in the conditions of pre-cycle, cycle I and cycle II, namely 50%: 77.27%: 100%. While the comparison of the minimum score in the pre-cycle conditions, cycle I and cycle II is 50: 65: 76, and the comparison of the maximum score in the pre-cycle conditions, cycle I and cycle II is 82: 90: 100. From the results of this study it can encourage class VI teachers. SD Inpres Tumpu Jaya I should be inspired to apply the cooperative script learning model in social studies learning because it has been proven to improve student social studies learning outcomes.